Nexus between exchange rate volatility and oil price fluctuations: Evidence from Pakistan - Rabia Ahmed; Imran Qaiser; Muhammad Rizwan Yaseen (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
Pakistan experienced too much variation in crude oil prices in the last decades and this variation received a great attention because it uses all the sectors of the economy. The purpose of this study is to ascertain the determinants of Real Exchange Rate and analyze the impact of Real Oil Price Volatility on Real Exchange Rate Volatility in Pakistan over 1983-Q1 to 2014-Q2. Various econometric techniques like Johansen Cointegration and Vector Error Correction Model have been used for short run and long run analysis respectively. Our findings explores that productivity differential, real foreign exchange reserves, interest rate differential, real exports and oil prices are the determinants of exchange rate. While, Real Foreign exchange reserves volatility, CPI volatility and Real Oil Price Volatility have positive and NEWS has a negative effect on Real Exchange Rate Volatility. Volatility results through EGARCH (1, 1) shows the presence of leverage effect in Real Oil Price Volatility and Real Exchange Rate Volatility. The government should make suitable policies for equilibrium of oil demand and supply in order to keep the exchange rate stable. Future research can be made on cross sectional countries by using monthly data of variables.
Keywords: 330; exchange rate; real exchange rate volatility; oil price fluctuations; impulse response; exponential generalize autoregressive conditional hetroscedasticity (EGARCH)